SOFTWARE DESIGN FOR LEARNING PROBLEMS MAID LAN - Rita Handayani; Ir Aqwam Rosadi K. (Jurnal Sistem Informasi, 1998)
LAN Local network problems and design to be used as teaching materials, as well as learning assistant in design software that can explain the material proposed for these courses. So that a problem using the strategy of separation between the substance with display own display will provide easiness